1992
DOI: 10.1111/j.1432-1033.1992.tb17195.x
|View full text |Cite
|
Sign up to set email alerts
|

Basement‐membrane heparan sulfate proteoglycan binds to laminin by its heparan sulfate chains and to nidogen by sites in the protein core

Abstract: A large, low-density form of heparan sulfate proteoglycan was isolated from the EngelbrethHolm-Swarm (EHS) tumor and demonstrated to bind in immobilized-ligand assays to laminin fragment E3, collagen type IV, fibronectin and nidogen. The first three ligands mainly recognize the heparan sulfate chains, as shown by inhibition with heparin and heparan sulfate and by the failure to bind to the proteoglycan protein core. Nidogen, obtained from the EHS tumor or in recombinant form, binds exclusively to the protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
1
4

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(152 citation statements)
references
References 40 publications
6
141
1
4
Order By: Relevance
“…4). These three niclogen interactions, which are mediated by different globular domains (G2, G3), have also been shown to mediate the formation of ternary complexes between the ligands using mouse nidogen as a connecting protein (Fox et al, 1991 ;Battaglia et al, 1992;Aumailley et al, 1993). Similar assays showed an activity for human nidogen comparable to that of mouse nidogen (Fig.…”
Section: Leucocytesupporting
confidence: 48%
See 3 more Smart Citations
“…4). These three niclogen interactions, which are mediated by different globular domains (G2, G3), have also been shown to mediate the formation of ternary complexes between the ligands using mouse nidogen as a connecting protein (Fox et al, 1991 ;Battaglia et al, 1992;Aumailley et al, 1993). Similar assays showed an activity for human nidogen comparable to that of mouse nidogen (Fig.…”
Section: Leucocytesupporting
confidence: 48%
“…Further binding sites of mouse nidogen for collagen IV and perlecan were found on its G2 domain (Battaglia et al, 1992;Reinhardt et al, 1993). Similar binding sites exist on human nidogen, although their affinities are somewhat lower when examined with mouse collagen IV and perlecan (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was particularly indicated from the binding properties of nidogen which can mediate the formation of ternary complexes between laminin, collagen IV and heparan-sul€ate proteoglycan (Fox et a]., 1991 ; Battaglia et al, 1992). Structural studies and cDNA sequencing have shown that mouse and human nidogen consist of a single, approximately 1200-residue polypeptide chain (Paulsson et al, 1986;Mann et al, 1989;Nagayoshi et al, 1989), and that nidogen and entactin, a protein obtained from a cellculture matrix (Carlin et al, 1981;Durkin et al, 1988), are identical.…”
mentioning
confidence: 99%